Cannabis use is both independently associated with and mediates worse psychosocial health in patients with epilepsy. Issue 8 (2nd March 2019) - Wahby, Sandra; Karnik, Vikram; Brobbey, Anita; Wiebe, Samuel; Sajobi, Tolulope; Josephson, Colin Bruce
Abstract : Objective: To examine whether cannabis use is associated with or mediates psychosocial health in people with epilepsy. Methods: Consecutive adult epilepsy patients visiting the Calgary Comprehensive Epilepsy Programme clinic were administered validated patient-reported outcome measures (PROMs) including the Neurological Disorders Depression Inventory for Epilepsy (NDDI-E), Quality of Life in Epilepsy (QOLIE-10-P), EuroQOL five dimensions five level scale (EQ-5D-5L), Global Assessment of Severity of Epilepsy Scale, Global Assessment of Disability Associated with Seizures Scale and the Treatment Satisfaction Questionnaire for Medication scale. We used multiple regression analyses to investigate associations between cannabis use and PROMs. Mediation analyses were performed to determine the degree to which cannabis modulated the associations between current or past psychiatric disorders, monthly seizure frequency, and 1-year seizure freedom on psychosocial health. Results: Of 337 consecutive patients, 71 (21%) reported cannabis use. Cannabis use was independently associated with depression (NDDI-E score≥14; OR 3.90; 95% CI 2.01 to 7.59; p<0.001), lower quality of life (β=−16.73, 95% CI − 26.26 to − 7.20; p=0.001), worse epilepsy-related disability (OR 2.23, 95% CI 1.19 to 4.17; p=0.01) and lower satisfaction with antiepileptic medication (OR 0.41, 95% CI 0.23 to 0.72; p=0.002). Cannabis use mediates 7%–12% of the effect of a psychiatric history on depression, worse quality of life and worse health valuation. Conclusions: There is a strong and independent association between cannabis use and poor psychosocial health, and it partially mediates the deleterious effect of a psychiatric history on these same outcomes. Inclusion of PROMs in future cannabis trials is warranted.